1995
DOI: 10.1144/gsjgs.152.4.0669
|View full text |Cite
|
Sign up to set email alerts
|

Two-stage deformation of the Mont-Louis-Andorra granite pluton (Variscan Pyrenees) inferred from magnetic susceptibility anisotropy

Abstract: The Mont-Louis-Andorra granodiorite pluton, Eastern Pyrenees (France, Andorra and Spain) was the subject of a thorough study of its internal structures, principally the measurement of the anisotropy of its magnetic susceptibility and the classification of its microstructures. Regularly spaced sampling (281 sites) allowed the precise mapping of the susceptibility magnitudes, consistent with mapped rock types. The magnetic structures fall into two distinct families which occur in separate parts of the pluton and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
1
3

Year Published

1997
1997
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(65 citation statements)
references
References 32 publications
3
58
1
3
Order By: Relevance
“…Thus, it can be proposed that granite emplacement took place under the same extension direction that is related to the normal fault movement. This contradicts the syntectonic character of the emplacement of the Andorra-Mont Lluís granite proposed by some authors [21,5] but is in strong agreement with the structural [23,11] and radiometric data [30] that points out that the granodiorite was emplaced well after the formation of the main Variscan contractional structures.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Thus, it can be proposed that granite emplacement took place under the same extension direction that is related to the normal fault movement. This contradicts the syntectonic character of the emplacement of the Andorra-Mont Lluís granite proposed by some authors [21,5] but is in strong agreement with the structural [23,11] and radiometric data [30] that points out that the granodiorite was emplaced well after the formation of the main Variscan contractional structures.…”
Section: Discussioncontrasting
confidence: 56%
“…From ASM and microstructure data Gleizes and Bouchez [21] and Bouchez and Gleizes [5] found two different microstructures affecting the Andorra-Mont Lluís granite. Family I is defined by a near horizontal NE-SW trending magnetic lineation, related to NW-SE oriented magnetic foliation ( [21] Plate I; [5], Figure 3). These authors interpreted this fabric as being due to near horizontal NE-SW shearing during magma emplacement.…”
Section: Discussionmentioning
confidence: 99%
“…Ferre et al, 2014). In a granitic pluton, the magnetic fabric pattern can be used to simulate the tectonic regime during the emplacement of the pluton (Bouchez and Gleizes, 1995;Aurejac et al, 2004;Talbot et al, 2005a and b;De Oliveira et al, 2010;Turrillot et al, 2011;Charles et al, 2012). In the Hengshan massif, a previous study has shown that the AMS fabric pattern of the mylonite is consistent with the mineral fabrics observed in the WHBF (Zhang and Zhu, 1989).…”
Section: Sampling and Measurementsmentioning
confidence: 99%
“…Thus, it is obvious that the suscepti bility in paramagnetic rocks depends on the iron content. As a result, it is possible to map the main phases in a paramagnetic granitic pluton based on the content of ferrous, silicate minerals, as in the case of the MontLouis-Andorre (Bouchez & Gleizes, 1995). Generally K m <50(tySI.…”
Section: Magnetic Susceptibility Of Granitic Rocksmentioning
confidence: 99%
“…Balsley & Buddington, 1960;Bouchez et al, 1990;Archanjo et al, 1994;Cruden & Launeau, 1994;Saint-Blanquat & Tikoff, 1997). Moreover, AMS has proved to be useful for the recognition of multiple deformation episodes in granitoids (Bouchez & Gleizes, 1995;Borradaile & Henry, 1997). Finally, it can be used in order to approach some environmental problems.…”
Section: Introductionmentioning
confidence: 99%